On the reinforcement of cement mortars through 3D printed polymeric and metallic fibers. (1st April 2016) - Farina, I.; Fabbrocino, F.; Carpentieri, G.; Modano, M.; Amendola, A.; Goodall, R.; Feo, L.; Fraternali, F.
Abstract: We employ additive manufacturing technologies for the design and fabrication of novel reinforcing elements of cement mortars. Three-point bending tests and optical microscope analyses are performed on a cement mortar reinforced with 3D printed fibers made of polymeric and metallic materials, which exhibit different surface morphology and roughness. Experimental and analytical results highlight that the shear capacity, flexural strength and fracture toughness of the examined materials greatly depend on the design and the material of the reinforcing fibers. Specimens reinforced with high surface roughness fibers exhibit shear failure and high interfacial bond strength, while unreinforced specimens and specimens reinforced with smooth fibers exhibit flexural failure and limited interfacial bond strength. We observe that mortar specimens reinforced with titanium alloy Ti6Al4V fibers exhibit load carrying capacity more than twice as high as specimens reinforced with photopolymeric fibers.